ANALISIS PENERAPAN SISTEM AKUNTANSI PENERIMAAN KAS DAN PENGELUARAN KAS PADA CV. PROSOLUTION MEDAN - Shalani Sabilla; Berupilihen BR Ginting (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
This study aims to find out what causes the payment of receivables, reports of cash disbursements and reporting of daily cash is not appropriate and late reporting. The method used is descriptive analysis, the data used is qualitative data, while based on the source using primary and secondary data. This study specifically discusses the functions, documents used, records used and procedures for receiving and disbursing cash at the company. There are still problems that arise in the cash receipts and disbursement accounting system implemented by CV. Prosolution, Medan. Based on the results of the data analysis conducted, it is known that the company uses flowcharts in cash receipts and disbursements. The purpose of this research is to implement a cash receipt and disbursement system at CV. Prosolution, Medan. The results showed that the cash receipts and disbursement accounting system was adequate, because it had implemented the functions, documents, methods and elements of cash receipts and disbursements properly, but the company had not implemented a predetermined flowchart.